Arm-hand BOOST (AHA-BOOST) therapy to improve recovery of the upper limb after stroke: rationale and description by means of the TIDieR checklist - Michielsen, Marc; Cornelis, Liesel; Cruycke, Lisa; De Smedt, Ann; Fobelets, Maaike; Putman, Koen; Vander Plaetse, Maaiken; Verheyden, Geert; Meyer, Sarah (Frontiers in Neurology, 2025)
PurposeThis methods article provides a detailed description of the Jessa AHA-BOOST program; an intensive, comprehensive, specific arm-hand therapy program for patients after stroke.Materials and methodsThe TIDieR (Template for intervention description and replication) checklist was used for the overview, which includes 7 topics: ‘Why’, ‘What’, ‘Who provided’, ‘How’, ‘Where’, ‘When and How much’ and ‘Tailoring’. Particularly the rationale for the program is extensively described.ResultsThe AHA-BOOST therapy program is developed for patients with mild to moderate impairments in the upper limb after stroke. It offers a 4-week tailored treatment program consisting of daily 1-h group sessions and weekly individual robot-assisted therapy. The sessions are built on neurophysiological and kinematic knowledge of reaching and grasping and on the principles of motor learning. The most important aspects in the content of the AHA-BOOST program are: (1) Neurophysiology; (2) Sequences of reaching and grasping; (3) De-weighting; and (4) Hand orientation.ConclusionIn a phase II RCT, the AHA-BOOST program proved to be feasible and safe and suggests positive, clinical meaningful effects on arm and hand function. A phase III RCT including clinical, health economic and process evaluations of the AHA-BOOST program is currently ongoing.